Case Study of Double-Wall Retaining Wall System for Deep Excavation in Jakarta, Indonesia - Anthony, Anthony; Wahyuningtyas, Indah Sri; Farkhantiansyah, Aggie (Indonesian Geotechnical Journal, 2024)
This paper presents a case study of diaphragm wall behavior in a deep excavation project under double-wall condition. A double-wall condition occurs when two layers of diaphragm wall, either side by side or with gaps between them, are used as a retaining wall system. The project discussed in this paper is located in a soft clay area of Jakarta, Indonesia, with a main excavation depth of approximately 33 meter and a side excavation depth of 23 meter. The project utilizes the top-down construction method, where the retaining walls for both the main and side structures are initially built before the excavation begins, creating the double wall condition. However, due to site issues, main excavation activities commenced after the construction of the main structure wall but before the side structure wall was completed, changing the plan to a single-wall condition. The behavior of the main structure wall under both single-wall and double-wall condition is studied. The study simulated two separate FEM models to evaluate the sequence of construction up to the final excavation level of the main station. According to the analysis result, single wall condition has relatively larger deformation than double wall condition. However, the wall bending moment did not change much, meaning that double-wall did not contribute effectively towards providing higher stiffness. The results contradict the initial assumption that the double-wall condition would be more advantageous for the main structure wall design than single-wall condition. Several critical parameters were found to significantly influence the outcome. The findings of this case study can provide valuable insights for the preliminary design of future excavation projects.